PENGARUH STRUKTUR MODAL TERHADAP KINERJA PERUSAHAAN DAN HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Binangkit, Bagas; Raharjo, Sugeng (STIE AUB Surakarta, 2014)
The purpose of this study is to examine the effect of capital structure on firm performance and stock price at a manufacturing company in Indonesia stock exchange. The population in this study is a manufacturing company which is listed on the Indonesian stock exchange with the study periode of 2007 â 2009, totaling 101 companies. Sample method is a purposive sampling to 41 companies. Mechanical testing data uses a regression analysis, paths analysis with significant level of 5% alpha. The result proved that the debt to Equity Ratio is positive and significant impact on Return of Assets, Debt to Asset Ratio is positive and significant impact on the Return Assets and Equity to Assets Ratio is negative but not significant effect on Return of Assets, debt to Equity ratio is positive and significant to direct effect on stock prices, Debt to assets ratio indirect is positive effect on stock prices. Equity to Assets Ratio indirect is positive effect on stock prices. The amount of R total of 0,999 means that the dependent variable (stock price) can be explained by the independent variables (debt to equity Ratio, Debt to Asset Ratio , Equity to Asset Ratio , Return on Assets)of 99,96% while 0,04% is explained by other factors not included in this study Keywords : Capital structure ( debt to equity ratio , debt to asset ratio , equity to assets ratio ) , firm performance ( return on assets ) , and stock prices